Physical-chemical indication for the implementation of a photometric flame method for determining calcium in parenteral solutions - Cognuck González, Sara (2017)
The investigative work consisted in the analytical investigation of a photometric proposal for the determination of calcium in five different parenteral solutions, in a laboratory (A) in the field of health in Costa Rica. First, the concentration of calcium present in the five parenteral solutions was determined by a volumetric method with EDTA in Laboratory A, the results of which were taken as reference since the method was validated by a body accredited for this purpose. Subsequently, the photometric method recommended by the photometer supplier was tested in the same Laboratory A, presenting problems of precision and accuracy; So we went to the tests in a laboratory B with an identical instrument, which did not give precision problems. The results from both laboratories were statistically compared with a t-Student test and it was stated that there is enough statistical evidence to say that the difference between the results of both laboratories is significant. However, irreversible interferences were maintained photometrically in the study matrices, determining that sodium causes an interference that generates greater intensity in the emission, producing a positive error in the expected calcium concentration. Finally, the suitability of the methodology to quantify calcium by flame photometry in another free sodium matrix was confirmed, obtaining satisfactory results for the calcium content.